1993
DOI: 10.1128/aem.59.4.1065-1071.1993
|View full text |Cite
|
Sign up to set email alerts
|

Role of growth phase and ethanol in freeze-thaw stress resistance of Saccharomyces cerevisiae

Abstract: The freeze-thaw tolerance of Saccharomyces cerevisiae was examined throughout growth in aerobic batch culture. Minimum tolerance to rapid freezing (immersion in liquid nitrogen; cooling rate, approximately 200'C min-') was associated with respirofermentative (exponential) growth on glucose. However, maximum tolerance occurred not during the stationary phase but during active respiratory growth on ethanol accumulated during respirofermentative growth on glucose. The peak in tolerance occurred several hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 36 publications
4
24
0
2
Order By: Relevance
“…For trehalose determination cells were harvested from 80 ml of culture and washed twice with chilled distilled water. Trehalose was extracted with cold 0.5 M trichloroacetic acid and estimated according to a modi¢ed anthrone procedure as previously described [14]. The content of trehalose was expressed as a percentage of the dry weight of cells.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…For trehalose determination cells were harvested from 80 ml of culture and washed twice with chilled distilled water. Trehalose was extracted with cold 0.5 M trichloroacetic acid and estimated according to a modi¢ed anthrone procedure as previously described [14]. The content of trehalose was expressed as a percentage of the dry weight of cells.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…The cell‐growth stage of yeast is an important factor in both cryopreservation and transformation. Yeast cells in the stationary phase generally become more resistant to cryoinjury and hypertonic stress than do those in the exponential phase (Morris et al ., 1988; Lewis et al ., 1993). It has been reported that compatible solutes such as glycerol and trehalose were transiently accumulated during the stationery phase (Gélinas et al ., 1989; Lewis et al ., 1993).…”
Section: Resultsmentioning
confidence: 99%
“…For the reasons mentioned above, the membrane water permeability responsible for thawing injuries is also an important factor in cryopreservation of competent cell for electroporation. The water permeability differs from strain to strain and is reflected by growth conditions such as growth phase and growth medium (Lewis et al ., 1993; Gélinas et al ., 1991). Therefore, transformation efficiency after cryopreservation would be influenced by the membrane permeability based on the strain and growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the exogenous glycerol was a less toxic cryoprotectant for yeast cells and enzyme. 38 The glycerol could affect lipid composition of the cell membrane by passive diffusion into the cell which could enhance the tolerance of the yeast to environment stress. 39,40 When the glycerol gets into the yeast, it could act as a carbon source which is metabolically phosphorylated to glycerol-3-P to form dihydroxyacetone-3-P after the oxidation.…”
Section: Discussionmentioning
confidence: 99%